Legality of Issuing a Certificate of Rights Land With Object in on Waters Sea (Studies Case Publishing Certificate Right Purpose Building Fence Sea in Tangerang) - Eddy Suharso; Gunawan Nachrawi; Jamiatur Robekha (Jurnal Info Sains : Informatika dan Sains, 2025)
Based on Law Number 27 of 2007 Jo. Law Number 1 of 2014 Concerning Management of Coastal Areas and Small Islands, the Government has the rights and controls. Regional governments, districts/cities have the responsibility to make plans for regulations or decisions in the management and utilization of resources for the benefit of the community. The issuance of land rights certificates on sea waters has a complicated background, involving legal aspects, regulations, and practices. In general, the sea is part of the natural resources controlled by the state, so it cannot be directly certified as land rights. However, there are exceptions for buildings or constructions built on waters, which can have land rights. The formulation of the problems discussed are: 1) What are the legal basis and legal considerations in issuing land title certificates with objects located above sea waters? and 2) How is the validity of land title certificates issued without meeting the requirements in the Complete Systematic Land Registration (PTSL)? The research method used is the normative touristic method, namely research that prioritizes library data, namely research on secondary data. The secondary data can be in the form of primary, secondary or tertiary legal materials. Based on the results of the study, the author concludes that the legal basis and legal considerations in issuing land title certificates with objects located above sea waters have a complex legal basis and require careful legal considerations. In general, land rights on land and at sea have different regulations, with the sea being considered a public space controlled by the state. Issuance of certificates for objects in sea waters often requires adjustments to regulations on licensing activities in sea space and considering the basic principles of agrarian law, namely: a) Basic Agrarian Law (UUPA); b) Law No. 27 of 2007 concerning Management of Coastal Areas and Small Islands; c) Government Regulation (PP) related to Sea Space; and d) Government Regulation No. 24 of 1997 concerning land registration. While the legal considerations are: a) Nationality Principle; b) State Control Rights; and c) Application of the HGB Principle (Building Use Rights) or Usage Rights.